Application Of Time Token Type Cooperative Learning Method In Improving The Ability To Write Poetry (Classroom Action Research) - Suherman, Achmad (International Journal of Artificial Intelligence Research, 2024)
This research aims to improve student learning outcomes in understanding poetry, namely through the Time Token Type method. The important role in improving students' ability to write poetry has become the main focus in replacing traditional teaching methods that have been going on for a long time. This research uses a classroom action research (PTK) approach, which includes descriptive analysis to motivate activity levels and achievement of learning outcomes by calculating average scores and percentages. In this research, the instruments used were observation sheets and tests. The learning process uses a time token type cooperative method which focuses more on understanding analysis and studying poetry. This method can also be applied by focusing on psychological aspects. The source of this research consisted of 30 students with 14 male students and 16 female students as part of the research sample. Based on the results of the research and discussion carried out, the researcher can conclude the following: it can be seen that the results of the implementation of classroom action (PTK) in cycle I are considered not successful and not in accordance with what was expected, that is, they have not reached the maximum level of learning completeness, so Efforts were made to improve learning in the second cycle and after the improvement efforts were made in this research, the results were significant changes, namely students' abilities were increasing, they were better at learning using the Time Token Type method. Based on the results of research in the pre-cycle, they got a percentage score of 36.66%, then learning In cycle I there was a change, namely getting a percentage score of 63.33% and in cycle II again there was a very significant increase, namely to 83.33%. The following can be described as several improvements in learning using the Time Token Type cooperative learning method as follows: 1). Students have a higher interest in reading poetry. 2). students' ability to write poetry becomes higher. 3). The interactive and communicative influence in learning on students becomes higher. 4). It is hoped that students' ability to create examples of poetry will increase, in this way it is hoped that this research will become literature or a reference to encourage experts in making policies to improve the quality of student learning, with several alternative learning models that refer to educational factors, namely cognitive, affective and psychomotor, especially the emphasis on student attitudes and behavior values, will be better